LOCAL GOVERNANCE IN AN INTERNATIONAL COMPARATIVE PERSPECTIVE COMPARING LOCAL GOVERNMENT FINANCES IN MACEDONIA WITH SLOVENIA - Elezi, Shiret (European Scientific Journal, ESJ, 2015)
Local Government finance is of immense importance for a state and for the government functions of rendering services to the citizens. Local finances reflect the fiscal independence of municipalities and the financial capacity to carry out its responsibilities under the legal provisions of the central government. It is therefore very important to monitor the development of local finance in transition countries and in transferring experiences from countries with higher fiscal decentralization to countries which are pre-accesion candidates to EU. Countries with higher fiscal decentralization are more acceptable bycountries that are recently new members of the European Union under similar region. In this study, a parallel overview of the local finances of new member country in the EU, Slovenia and pre-accesion candidate country to the EU i.e. Macedonia, was taken